A single-dose, randomized, open-label, four-period, crossover equivalence trial comparing the clinical similarity of the proposed biosimilar rupatadine fumarate to reference Wystamm® in healthy Chinese subjects - Lin, Sisi; Lou, Yutao; Hao, Rui; Shao, Yiming; Yu, Jin; Fang, Lu; Bao, Meihua; Yi, Wu; Zhang, Yiwen (Frontiers in Pharmacology, 2024)
Purpose The aim of this study was to evaluate the bioequivalence of two formulations of rupatadine (10-mg tablets) under fasting and fed conditions in healthy Chinese subjects. Methods A total of 72 subjects were randomly assigned to the fasting cohort (n = 36) and fed cohort (n = 36). Each cohort includes four single-dose observation periods and 7-day washout intervals. Blood samples were collected at several timepoints for up to 72 h post-dose. The plasma concentration of rupatadine and the major active metabolites (desloratadine and 3-hydroxydesloratadine) were analyzed by a validated HPLC–MS/MS method. The non-compartmental analysis method was employed to determine the pharmacokinetic parameters. Based on the within-subject standard deviation of the reference formulation, a reference-scaled average bioequivalence or average bioequivalence method was used to evaluate the bioequivalence of the two formulations. Results For the fasting status, the reference-scaled average bioequivalence method was used to evaluate the bioequivalence of the maximum observed rupatadine concentration (Cmax; subject standard deviation > 0.294), while the average bioequivalence method was used to evaluate the bioequivalence of the area under the rupatadine concentration–time curve from time 0 to the last detectable concentration (AUC0-t) and from time 0 to infinity (AUC0-∞). The geometric mean ratio (GMR) of the test/reference for Cmax was 95.91%, and the upper bound of the 95% confidence interval was 95.91%. For AUC0-t and AUC0-∞ comparisons, the GMR and 90% confidence interval (CI) were 98.76% (93.88%–103.90%) and 98.71% (93.93%–103.75%), respectively. For the fed status, the subject standard deviation values of Cmax, AUC0-t, and AUC0-∞ were all <0.294; therefore, the average bioequivalence method was used. The GMR and 90% CI for Cmax, AUC0-t, and AUC0-∞ were 101.19% (91.64%–111.74%), 98.80% (94.47%–103.33%), and 98.63% (94.42%–103.03%), respectively. The two-sided 90% CI of the GMR for primary pharmacokinetic endpoints of desloratadine and 3-hydroxydesloratadine was also within 80%–125% for each cohort. These results met the bioequivalence criteria for highly variable drugs. All adverse events (AEs) were mild and transient. Conclusion The test drug rupatadine fumarate showed a similar safety profile to the reference drug Wystamm® (J. Uriach y Compañía, S.A., Spain), and its pharmacokinetic bioequivalence was confirmed in healthy Chinese subjects based on fasting and postprandial status. Clinical trial registration: http://www.chinadrugtrials.org.cn/index.html, identifier CTR20213217